2007
DOI: 10.1016/j.cell.2007.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The XIST Noncoding RNA Functions Independently of BRCA1 in X Inactivation

Abstract: Females with germline mutations in BRCA1 are predisposed to develop breast and ovarian cancers. A previous report indicated that BRCA1 colocalizes with and is necessary for the correct localization of XIST, a noncoding RNA that coats the inactive X chromosome (Xi) to mediate formation of facultative heterochromatin. A model emerged from this study suggesting that loss of BRCA1 in female cells could reactivate genes on the Xi through loss of the XIST RNA. However, our independent studies of BRCA1 and XIST RNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 43 publications
7
60
1
Order By: Relevance
“…Unfortunately, this does not shed light on how XIST deregulation or the loss of an inactive X chromosome confers a resistance phenotype. A link between BRCA1 and XIST has been investigated intensively (35)(36)(37)(38)(39). Furthermore, the deletion of Xist in mice leads to hematologic malignancies (40) and genomic instability of the X chromosome (41).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this does not shed light on how XIST deregulation or the loss of an inactive X chromosome confers a resistance phenotype. A link between BRCA1 and XIST has been investigated intensively (35)(36)(37)(38)(39). Furthermore, the deletion of Xist in mice leads to hematologic malignancies (40) and genomic instability of the X chromosome (41).…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that loss of BRCA1 in female cells may lead to destabilization of X chromosome. However, Xiao et al found that XIST functions independently of BRCA1 in X inactivation (88). According to results of Livingston group, the loss of BRCA1 in female cells could reactivate genes on the inactive X chromosome due to loss of XIST (87); however, the reason of this apparent controversy is not clear.…”
Section: Xist-xistmentioning
confidence: 85%
“…According to results of Livingston group, the loss of BRCA1 in female cells could reactivate genes on the inactive X chromosome due to loss of XIST (87); however, the reason of this apparent controversy is not clear. They also found that BRCA1 was not enriched on XIST RNA-coated chromatin of inactive X chromosome (88). To respond to these findings, Livingston group showed further evidences of BRCA1's communication with inactive X chromosome (89).…”
Section: Xist-xistmentioning
confidence: 93%
“…When transcribed, BRCA1 then guides Xist to reinteract with and therefore re-silence the same chromosome (Ganesan et al, 2004;Ganesan et al, 2002;Silver et al, 2007). However, this is not a universal finding (Pageau et al, 2007;Xiao et al, 2007).…”
Section: Potential Significance Of X Chromosome Location Of Mir-106amentioning
confidence: 96%